Agricultural extension services: study visit - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
workshop to discuss the challenges facing agricultural extension services in Africa was organized in January, 1994 by CTA in collaboration with the Agricultural University of Wageningen. The workshop was held in Yaoundé, Cameroon